Analysis of TCR Vβ2+T cells and HLA-DRB1, TNF-α and ITPKC gene profiles of Filipino kawasaki disease patients - Natividad, Magdalena F. (National Institute of Molecualr Biology and Biotechnology, College of Science, University of the Philippines Diliman, 2013)
Kawasaki disease (KD) is an acute febrile, multisystem vasculitis most frequently affecting young children that may result in the development of coronary aneurysm and other cardiac complications. KD etiology is unknown but is believed to be caused by an infectious agent with possible involvement of a superantigen (SAg) may also be involved. A hallark of SAg driven disease is an increase in the number of T cells expressing a specific T cell receptor (TCR) V beta region such as Vβ2. Based on the epidemiologic features of KD, genetic factor have been proposed to be associated with susceptibility to the disease.This study aimed to determine if there is a difference in the percentage of TCR-Vβ2+ T cells between KD patients and healthy controls which may suggest SAg involvement.In addition, DNA polymorphisms in the exon 2 of HLA DRB1, the promoter region of TNF-α and the functional SNP (rs28493229) of intron 1 in inositol1,4,5-triphosphate-3 kinase-C (ITPKC) gene are analyzed for their association with KD susceptibility. The percentages of Vβ2+ Tcells in KD patients and in healthy controls were compared by flow cytometry using anti-Vβ2 monoclonal antibody. Results revealed that there is a statistically significant difference in the percentages of Vβ2+ T-cells between KD patients (9.5 ± 2.15%) and healthy controls (7.25 ± 1.48 %) (P<0.05, Student's t-test, n=6-8/group).However, no polymorphisms were observed in exon 2 of HLA-DRB1 and in the -308 region of the TNF- α promoter. The ITPKC SNP rs28493229 G/C polymorphism was observed in 1 KD patient and 4 healthy controls. This study suggests that a SAg may be involved in the etiology of KD and that HLA-DRB1 exon2, TNF-α -308 region and ITPKC SNP rs28493229 may not e associated with KD. This is the first study investigating Vβ2+ T cells and candidate genes involvement among Filipino KD patients.